Study on the podophyllotoxin in the Dysosma versipellis (Hance) M. Cheng and its Callus' Materials - PAN Qi; CHEN Shao-yuan; JIANG Wei-mei; Gilbert Y S Chan; FU Cheng-xin (浙江大学学报. 农业与生命科学版)
In this study, HPLC was used to detect the podophyllotoxin content in three parts of Dysosma versipellis (Hance). The content was 0.60% in the wild root, while in the calli and the induced root from this calli, they were 0.117% and 0.148%, respectively. The results suggest that it is possible to produce podophyllotoxin quickly by tissue culture, and provide much raw material to antitumor drugs with little damage to the natural resources.